Assessing the earthquake hazard around the Río de la Plata estuary (Argentina and Uruguay): Implications for risk assessment. (December 2021) - Baxter, Peter; Bettucci, Leda Sánchez; Costa, Carlos H.
Abstract: Approximately 18 million people live around the Río de la Plata estuary. Being far away from the zones of major plate boundary-related earthquakes in South America, this region is conventionally regarded as being seismically stable. Nevertheless, during the last 2 centuries of recorded history, there have been several earthquakes of low to moderate magnitude in the region and there is no reason to suppose that it will not continue to be seismically active, albeit at low to moderate levels. This paper examines the evidence and reviews the seismic hazard for the areas bordering the Río de la Plata, and, taking into account the lack of preparedness in terms of construction codes, specifically in Uruguay, concludes that the exposure risk needs review. Until further investigation is carried out, we recommend that consideration be given to raising the seismic hazard rating for the zone around the Río de la Plata estuary to a PGA level of 0.1 g for 10 % probability of exceedance in a 50 year period. Highlights: Review of historical seismicity around Río de la Plata. Estimates of probabilistic seismic hazard for Montevideo and Buenos Aires. Recommends interim hazard rating of 0.1 g for 70 km inland from Río de la Plata coast. Recommendations for further investigation and refinement.